Reducing Production Costs and Its Impact on the Continuity of the Project - Dr. Amina Ibrahim Khalf; Dr. Emad Moafaq Abed; Dr. Khawala Hadi Utaiwi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Because of the developments in the business environment as a result of economic and technological openness, which resulted in these developments an increase in competition between economic units, and thus this led to an increase in competition between economic units, which led to high costs of their products as they do not take into account the requirements of customers and their tastes, which prompted this Units need to search for adequate means to help them keep pace with the changes that happen and thus improve their competitive position, which greatly contributes to the continuity of these units among other economic units, and in order to achieve this, they must undertake the process of reducing the costs of their products without compromising the quality and quality of the product and thus have reached this The study concluded with several conclusions, the most important of which was the philosophy of reducing costs as a primary goal for industrial companies that seek to maintain their competitive edge and continuity over the long term. The most important recommendations were urging industrial companies in Iraq to apply modern and computer cost programs in a sound and systematic manner in order to achieve the highest level of efficiency and effectiveness. For those systems and make use of them to a maximum degree to reduce the cost of the product, which in turn Helps to continue the project for a longer period.